Study on the Optically Transparent Near-Field and Far-Field RFID Reader Antenna - Yuan Yao; Junsheng Yu; Xiaodong Chen (International Journal of Antennas and Propagation, 2014)
A study on the optically transparent RFID reader antenna which can operate in both near-field and far-field is proposed in this paper. The antenna with a dimension of 45 mm × 45 mm is fabricated using Indium tin oxide film and can operate from 915 to 935 MHz covering the China UHF RFID band. The strong and uniform magnetic field is excited by magnetic dipole source. Both simulation and measurement results are shown to illustrate the performance of the proposed antenna. The measured reading distances are up to 40 mm and 100 mm for near-field and far-field applications, respectively.